2002
DOI: 10.1007/s11746-002-0477-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of female and male genotypes and environment on wax composition in jojoba

Abstract: The objective of this study was to determine the effects of genotype and environment on wax composition in jojoba seed, and thus be able to control it. Production of waxes with different compositions-and hence changed wax properties such as viscosity, boiling point, and thermal stability-may be of importance for future requirements of the jojoba industry. Wax composition of 23 female clones was determined for two growing seasons. The ratio of FA elongated to the sum of those reduced and esterified differed amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In the present study a reliable jojoba male-specific marker was identified. In jojoba breeding studies the genetic properties of the male and female should be considered since the effect of the male and female parents on yield and wax compositions are additive and highly significant (Benzioni and Vaknin 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study a reliable jojoba male-specific marker was identified. In jojoba breeding studies the genetic properties of the male and female should be considered since the effect of the male and female parents on yield and wax compositions are additive and highly significant (Benzioni and Vaknin 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The economic value of jojoba comes from its seeds which contain about 50-60% of a light yellow, odorless wax ester commonly referred to as jojoba oil. As many as 300 products containing jojoba have appeared in markets in recent years and the use of jojoba products will increase in future (Benzioni and Vaknin 2002;Benzioni et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The approximate FA composition of JO oil, consisting for 98% of monounsaturated ω-9 FAs, is 66-71% C20:1 (cis-11-eicosenoic acid), 14-20% C22:1 and 10-13% C18:1 [284]. The fi nal composition of this unique storage-lipid wax is a result of activities and affi nities of three main enzymes: a fatty acyl-CoA elongase (β-ketoacyl-CoA synthase), which produces 20 : 1, 22 : 1 and 24 : 1 acyl CoA as precursors to the wax; fatty alcohol reductases (acyl CoA reductases); and acyl : alcohol transacylase [285].…”
Section: Bio-based Wax Estersmentioning
confidence: 99%
“…However, a period of 3-6 years would be required for the new male plants to produce sufficient pollen to be effective. Furthermore, the selection of male plants for plantations requires genetic knowledge about them, since the effect of the male and female parents on yield and wax compositions are additive and highly significant (Benzioni & Vaknin 2002).…”
Section: Introductionmentioning
confidence: 99%